Prevalence of Genarchopsis dasus (Digenea: Hemiuridae) in Channa punctatus of Mymensingh (Bangladesh Veterinarian, 2011)
An investigation was made on prevalence of the parasite Genarchopsis dasus in the fish Channa punctatus of Mymensingh, Bangladesh to determine the infestation and seasonal variation. The experiment was carried out from December 2009 to November 2010. A total of 379 parasites were collected from 235 host fish. The prevalence of G. dasus was higher in July and lower in September and October. The highest prevalence (83.3%) was in rainy July and lower in September and October. The highest prevalence (83.3%) was in rainy season and the lowest (45.5%) in autumn. The highest intensity of G. dasus was in July and the lowest in December, and the highest and lowest intensity was in rainy and winter seasons, respectively. The prevalence was highest in intermediate length fish (67.0%), where the lowest (54.9%) was in small fish. Intensity was highest in intermediate length fish. The higher prevalence (90%) and intensity (4.3) was in female during rainy season. The lower prevalence (32%) and mean intensity (1.1) was in male during autumn. The highest ratio of mature: immature was in summer (30 : 37), the highest percentage of mature worms was in summer and the highest proportion of immature worms in autumn. The stomach contained most worms (72.8%) and the lowest proportion (6.6%) was in anterior portion of intestine. DOI: http://dx.doi.org/10.3329/bvet.v28i1.8813   Bangl. vet. 2011. Vol. 28, No. 1, 47-54